Central Giant Cell Granuloma of the Jaws: Correlation between Vascularity and Biologic Behavior - Saede Atarbashi Moghadam; Maedeh Ghorbanpour (Mashhad University of Medical Sciences, 2017)
Introduction: Giant cell lesions of the bone comprise a group of jaw bone pathologies. Different pathogeneses such as reactive, vascular or neoplastic have been proposed for these lesions. In addition, differentiating between aggressive and nonaggressive central giant cell granuloma (CGCG) of the jaws based on histopathologic features is still impossible and due to different treatment protocols for the two groups, correct diagnosis is necessary. The purpose of this study was to compare the expression of CD34 between aggressive and nonaggressive CGCGs of the jaws. Methods & Materials: This retrospective study was carried out on 16 paraffin blocks in each aggressive and nonaggressive CGCGs group. The expression of CD34 was evaluated with immunohistochemical technique. Afterwards, t-test was used for quantitative evaluation and comparison of CD34 expression among the two groups. Eventually, statistical analysis was performed using Spss20 software. Significance was assigned at p < 0.05. Results: In the present study, the average age of patients in aggressive and nonaggressive groups was 20.93±8.08 and 26.18±16.97, respectively. In both groups, female predilection was observed. Mandible was the most common site of involvement in the aggressive group and the distribution of nonaggressive lesions was equal between both jaws. Although the expression of CD34 in the aggressive group was higher than the nonaggressive group, no statistically significant difference was seen (p=0.15). Conclusion: According to the results of the current study, it appears that CD34 protein cannot be used for identifying the clinical behavior of CGCGs.